A Critical Analysis of Resource Sharing and Networking of SLSTINET Activities - Rifaudeen, M.M. (DEGREE OF MASTER IN LIBRARY AND INFORMATION SCIENCE, 2002)
The research study intends to examine whether the SLSTINET stands to serve the member institutions to meet the Expectations of them. The researcher is therefore to study the present situation of resource sharing and networking activities prevailing among SLSTINET libraries and to evaluate the effectiveness of SLSTINET. Having examined the data obtained in detail the study, consequently had proposed an innovative model and some feasible recommendations to develop the SLSTINET as an effective library network to serve the purpose. The evaluation of the SLSTINET was conducted based on its objectives and selected criteria. The Likerfs Method of summated stating has been used to measure the objectives statement of the SLSTINET. The effectiveness of the SLSTINET has been assessed by using chi-square test with 95% confidence level. For data collection 02 different structured questionnaires has been used. The study has found out the effectiveness of the SLSTINET is as 59.13% + 4.24% at 95% confidence level. As its effectiveness is found above 50%. so it is recommended to continue the network as worthwhile in the light of the recommendations given in this research study.